ANALISIS KEBUTUHAN SEKOLAH DASAR DI BANTEN BERDASARKAN INDIKATOR PENDIDIKAN DAN FISKAL - Prabowo, Sakti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study develops an Urgency Index for Primary School Needs to assess disparities in basic education provision across districts and cities in Banten Province, Indonesia. The index integrates indicators of educational access, infrastructure availability, teacher adequacy, demographic pressure, and local fiscal capacity. Using a quantitative descriptive approach with composite index modeling, the study identifies regions that require priority intervention under the national Sekolah Rakyat initiative. The analysis shows substantial inequalities in school capacity and access across Banten. Tangerang Regency, Tangerang City, and Serang City occupy the top three priorities for primary school development. Tangerang Regency has the first priority because it has the highest number of out-of-school children in the Banten region, proportional to the number of children aged 5-14 years, plus the highest student/teacher ratio, and is supported by high fiscal capacity. Tangerang City has the second priority because it has a large number of children aged 5-14 years, has a relatively high number of out-of-school children, and is supported by high fiscal capacity. Serang City has the third priority because it has a relatively low literacy index, with a relatively low School Participation Rate, and a relatively high student/teacher ratio.